COD capture: a feasible option towards energy self-sufficient domestic wastewater treatment - Wan, Junfeng; Gu, Jun; Zhao, Qian; Liu, Yu (Scientific reports, 2016)
Although the activated sludge process, one of the most remarkable engineering inventions in the 20 th century, has made significant contribution to wastewater reclamation in the past 100 years, its high energy consumption is posing a serious impact and challenge on the current wastewater industry worldwide and is also inevitably linked to the issue of global climate change. In this study, we argued that substantial improvement in the energy efficiency might be no longer achievable through further optimization of the activated sludge process. Instead, we should devote more effort to the development or the adoption of novel treatment configurations and emerging technologies. Of which an example is A-B process which can significantly improve the energy recovery potential at A-stage, while markedly reduces energy consumption at B-stage. Various configurations of A-B process with energy analysis are thus discussed. It appears highly possible to achieve an overall energy gain in WWTPs with A-B process as a core.